The Impact of Autism Spectrum Disorder on Parents in Arab Countries: A Systematic Literature Review - Alkhateeb, Jamal M.; Hadidi, Muna S.; Mounzer, Wissam (Frontiers in Psychology, 2022)
Abstract Background: Having a child with autism spectrum disorder can have significant psychological affects on parents. This systematic review summarizes the current state of literature underscoring the impact of autism spectrum disorder (ASD) on parents in Arab countries Methods: A systematic search of seven databases (PubMed, Scopus, ProQuest, Google Scholar, ERIC, Academic Search Complete, and PsycINFO) was performed, which identified 24 studies (20 quantitative studies and four qualitative studies) that included 3,299 parents or caregivers of children with ASD. These studies were conducted in 10 Arab countries (Saudi Arabia, Jordan, Egypt, Kuwait, Bahrain, Oman, Emirates, Palestine, Qatar, and Lebanon). Results: The majority of the included studies found that ASD has a significant negative impact on the mental health and well-being of Arab parents. It was found that parents of children with ASD have a poor quality of life (QoL) and an increased risk of psychological disorders. These findings were in contrast to findings of parents of typically developing children and children with other developmental disorders. Challenges faced by parents of children with ASD were associated with several child- and parent-related factors. The most common coping strategy used by parents was religious coping. Conclusion: The impact of ASD on parents has only recently gained traction among researchers in Arab countries. Despite several knowledge gaps, published studies have provided useful information outlining the impact of ASD on parents in some of these countries. Further research comprising larger random samples and using varied research and data-collection methods is required to understand the multifaceted challenges experienced by parents raising children with ASD in Arab countries.